MENGHIDUPKAN NILAI AGAMA: UPAYA MEMBANGUN MORALITAS KEKUASAAN DAN MASYARAKAT MADANI. - Mujtahid, Mujtahid (Jurnal Bestari, 2001)
Beside as a faith, religion is the absolute and universal sources of spirit and value. As a spirit and value, religion could be used as teh ethic fremes for delvelop of the power morality and civil society. Most Moslem scholars said that religion is the ethic frame to solve thr social problems. This article tends to discuss a bout power morality and civil society in the sight of religious values. Since as a value laded, religion must could be understand as the life-principles, include as apower and social system. Reflection which rise from religious society is the shaping of power legality and civil society.